2016
DOI: 10.1016/j.ijhydene.2015.10.119
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the transmitted noise of a combustor exit nozzle caused by burned hydrogen-hydrocarbon gases

Abstract: Transmitted noise is a major problem in industrial and aero-engine gas turbines. One of a noise generating part in the preceding systems is exit nozzle which can play as encouraging or discouraging sound waves. The generated noise may arise from an incident acoustic wave or entropy wave. In this paper, the effect of heat transfer and inlet Mach number of the exit nozzle as well as replacing the traditional hydrocarbon fuels with hydrogen and composite of hydrogen-hydrocarbon on noise generation is studied. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The results showed that the non-compact nozzle theory is necessary to accurately capture phase-cancellation effects between entropy and composition noise, and the linearized Euler formulation is required to account for complex mode shapes of the perturbations exiting the combustor and entering the downstream nozzle. The entropy dispersion effects on the combustion noise level of a combustor and turbine outlet were studied by Mahmoudi et al [34] and Fattahi and co-workers [35][36][37]. They reported that entropy dispersion is an important factor to increase the level of noise emission in turbines and nozzles.…”
Section: -Introductionmentioning
confidence: 99%
“…The results showed that the non-compact nozzle theory is necessary to accurately capture phase-cancellation effects between entropy and composition noise, and the linearized Euler formulation is required to account for complex mode shapes of the perturbations exiting the combustor and entering the downstream nozzle. The entropy dispersion effects on the combustion noise level of a combustor and turbine outlet were studied by Mahmoudi et al [34] and Fattahi and co-workers [35][36][37]. They reported that entropy dispersion is an important factor to increase the level of noise emission in turbines and nozzles.…”
Section: -Introductionmentioning
confidence: 99%
“…Recently, a number of attempts have been made to release some of the simplifying assumptions of this work. These include considering nonlinear perturbations in the compact limit [24], noncompact nozzles [25,26], piecewise-linear mean velocity profiles [27] and finite wave frequency [28].…”
mentioning
confidence: 99%
“…The seminal work of Marble and Candel [5] on the conversion of entropy waves to acoustic perturbations commenced the research activities around indirect noise and, remained as a key reference for more than forty years. Following a few decades of gap, many efforts was made to release the simplifying assumptions of the model of Marble and Candel [5] such as linear wave and compact nozzle [16][17][18][19][20][21]. Yet, the assumption of one-dimensionality of entropy wave remained as an essential element of these analyses.…”
mentioning
confidence: 99%
“…This is especially the case when entropy waves reach the first stage of turbine blades that are essentially nozzlelike passages. The existing studies indicate that the state of flow has a pronounced effect upon the entropy wave [19,20,28,39]. Although fluid flow in a nozzle is significantly different to that in a straight duct, so far all studies on the dynamics of entropy waves have been focused on straight channels [9,14, ,36,40,41].…”
mentioning
confidence: 99%